Modeling, simulation and coupling experiment for integrated passive wireless multi-parameters ceramic sensor. Issue 1 (18th January 2016) - Wei, Tanyong; Tan, Qiulin; Luo, Tao; Wu, Guozhu; Tang, Shun; Shen, Dan-Dan; Li, Chen; Xiong, Jijun
Abstract : Purpose: – The purpose of this paper is to propose a pressure-, temperature- and acceleration-sensitive structure-integrated inductor-capacitor (LC) resonant ceramic sensor to fulfill the measurement of multi-parameters, such as the measurement of pressure, temperature and acceleration, simultaneously in automotive, aerospace and aeronautics industries. Design/methodology/approach: – The ceramic-based multi-parameter sensor was composed of three LC tanks, which have their resonant frequencies sensitive to pressure, temperature and acceleration separately. Two aspects from the specific sensitive structure design to the multiple signals reading technology are considered in designing the multi-parameter ceramic sensor. Theoretical analysis and ANSYS simulation are used in designing the sensitive structure, and MATLAB simulation and experiment are conducted to verify the feasibility of non-coverage of multi-readout signals. Findings: – It is found that if the parameters of sensitive structure and layout of the LC tanks integrated into the sensor are proper, the implementation of a multi-parameter sensor could be feasible. Practical implications: – The ceramic sensor proposed in the paper can measure pressure, temperature and acceleration simultaneously in harsh environments. Originality/value: – The paper creatively proposes a pressure-, temperature- and acceleration-sensitive structure-integrated LC resonant ceramic sensor for harsh environments and verifies the feasibility of the sensor from sensitive structure design to multiple-signal reading.